Hiking waterfalls Oregon : a guide to the state's best waterfall hikes - Sawyer, Adam, 1974- (FalconGuides, 2020)
"This beautiful, full-color guidebook features 64 of the best waterfall hikes in Oregon, with another 19 honorable mentions. From the Coast Range to the Cascades, along with the breathtaking Columbia River Gorge, you can explore those special places where water cascades over cliffs. Some waterfalls are remote while others are just a short hike from the trailhead, some are gentle trickles and others are roaring giants. Yet all of them offer a peaceful escape and are worth seeking out."--Amazon.com.